Economics at the End of Life: Hospital and ICU Perspectives - Zilberberg, Marya D.; Shorr, Andrew F. (Seminars in Respiratory and Critical Care Medicine, 2012)
Not all feasible care is desirable care. At the end of life, aggressive interventions may not only be futile but also inappropriate because they may impair the quality of the remaining life for both the patient and the caregiver. Although it is challenging to identify patients with a poor prognosis, certain terminal conditions among the elderly, such as end-stage dementia, heart failure, and metastatic cancer, demand a more measured use of aggressive care. Frank discussions with patients and family about their desires in the context of the prognosis, as well as symptom support, can yield both economic savings and better quality of life.
Keywords: end-of-life care; futile care; intensive care unit; palliative care; health care economics